A new perspective of environmental behaviour study: a brief introduction of Wi-Fi indoor positioning system. (3rd April 2019) - Lin, Yuming; Huang, Weixin
Environment behaviour study is fundamental to architectural and urban design. The traditional methods have difficulty in obtaining quantitative data on a large-scale, which indirectly hinders the intelligent process of building environment. The newly developed Wi-Fi indoor positioning system can provide a large number of effective data to environment behaviour study. This study gives a brief introduction to the Wi-Fi positioning system and analyses the abundant information contained in its data. On this basis, this study takes an innovation incubator as an example, trying to explore human interaction in the environment with the tool of social network analysis. Finally, this study provides a simple framework for implementing smart home with positioning data. The conclusions highlight the advantages and limitation of Wi-Fi positioning system, as well as the promising prospect in the smart home.